Psychological roots of political consumerism: personality traits and participation in boycott and buycott - Ackermann, Kathrin; Gundelach, Birte (Sage, 2022)
Political consumerism is currently one of the most prevalent forms of non-institutionalized political engagement in Western democracies. This article aims to understand its psychological roots. We expect interindividual differences in psychological dispositions to be particularly relevant for political consumerism due to the individualized and cause-oriented nature of this form of political action. Our empirical evidence supports this claim: Open people favour, and conscientious people avoid, boycotting and buycotting. Agreeable persons tend to avoid boycotting in particular. These relationships persist even when political and social attitudes are controlled for. Thus, we show that psychological factors play an important role in shaping politically conscious consumption behaviour. At the same time, our study points out that personality profiles vary across different forms of political consumerism and modes of political action more generally. The characteristics of the diverse modes may help to understand this variation.
In: International Political Science Review, 43 (2022), Nr. 1. pp. 36-54. ISSN 0192-5121 (Druck-Ausg.), 1460-373X (Online-Ausg.)